2013
DOI: 10.1186/1471-2318-13-110
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the mobility of residents with dementia: a pilot study promoting healthcare aide uptake of a simple mobility innovation in diverse nursing home settings

Abstract: BackgroundAlmost 90 percent of nursing home residents have some type of mobility limitation. Many spend most of their waking hours lying in bed or sitting. Such inactivity can negatively affect residents’ health and general well-being. This pilot study aimed to assess (1) the effect of the sit-to-stand activity on mobility outcomes of nursing home residents, (2) the effect of an audit-and-feedback intervention on uptake of the sit-to-stand activity by healthcare aides, and (3) the contextual factors influencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 57 publications
0
29
0
Order By: Relevance
“…Not all eligible residents were contacted by the researchers; if they reached the 20 patient quota per home, the remaining list of eligible participants who had agreed to be approached by researchers was not exhausted. As resident participation rates for Canadian LTC research ranges from 65–72% [8385], M3 had a successful participation rate which is attributed to the relationship building, training of home and research staff, as well as the non-invasive protocol. Participants were representative of the units where they lived.…”
Section: Discussionmentioning
confidence: 99%
“…Not all eligible residents were contacted by the researchers; if they reached the 20 patient quota per home, the remaining list of eligible participants who had agreed to be approached by researchers was not exhausted. As resident participation rates for Canadian LTC research ranges from 65–72% [8385], M3 had a successful participation rate which is attributed to the relationship building, training of home and research staff, as well as the non-invasive protocol. Participants were representative of the units where they lived.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that simple interventions such as this could be integrated into the daily work routines of UCPs to slow decline in mobility and function in ADLs for residents with dementia (Slaughter et al., ). Other studies have explored the UCP role in diabetes management (Vincent et al., ), health promotion (Johnson & Noel, ), therapeutic recreational programmes (Sullivan & Sharpe, ), physical mobility (Slaughter & Estabrooks, ) and palliative care (Kaasalainen, Brazil, & Kelley, ). Table categorises tasks into the categories of (i) ADL & IADL tasks; (ii) housekeeping tasks; (iii) complex tasks delegated by regulated professionals; (iv) observation and documentation of clinical measures; and (v) additional tasks that promote independence and quality of life.…”
Section: Resultsmentioning
confidence: 99%
“…instrumental support (e.g., buy supplies in advance) provided by family caregivers lead to a positive work experience -Creating additional workload (e.g., tasks not about the patient) and lack of respect for the work done by home support workers lead to a negative work experience 54. Slaughter & Estabrooks. (2013) Experimental study Residential long-term-care -Sit-to-stand activity helped residents with dementia maintain mobility and slowed functional decline…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While 18.5% (n = 381) of the participants were completely independent of mobilisation assistance from others, 23.0% were almost independent, 19.2% partly dependent, 15.5% nearly dependent, and 23.8% completely dependent, a total of 81.5% (n = 1,673). Thus, qualitative statements such as "the majority of nursing home residents have a mobility disability" [8] could be quantified, and the estimate of Slaughter et al [47] that 90% of the residents have mobility disabilities can now be specified. The current study also quantifies the high demand for support for nursing home residents, which is usually provided by other people and in RCFs, mainly by caregivers.…”
Section: Hypothesismentioning
confidence: 99%